Sex-Dependent Physiological and Metabolic Alterations in Chronic Renal Failure: Insights from an Iraqi Cohort - Al‑Hamadani, Mohammed Y. I. (American Journal of Biology and Natural Sciences, 2025)
Chronic renal failure (CRF), commonly known as chronic kidney disease (CKD), is a progressive, irreversible decrease of kidney function that eventually necessitates dialysis or a kidney transplant. Among male and female CRF patients, immune markers (IgG, IgA), liver function enzymes (AST, ALT and ALP) from major biochemical parameters such as Urea, Creatinine, UA Ca2+, Na+ K+, Cl- were measured. Overall, 90 individuals were enrolled: 60 patients (≥25 years, both sexes) and 30 age-matched healthy volunteers (≥28 years). CRF patients had considerably higher immunoglobulins G and A with female preponderance (63.3%). The latter showed increased liver enzyme activities, together with several remarkable alterations in biochemical parameters when compared to controls. An interesting finding was the possible association of celiac disease with a propensity of CKD. The positive results from the present investigation suggest that consideration of these hepatic immune and metabolic markers tested for should be included within patient-based early diagnosis. Disease severity and complications can be predicted by means of these simple, rapid measurements. Such a timely diagnosis is of great significance for the health care providers and decision makers, with better prediction to have a better prognosis and slow down the progression of CKD.